Relationships between soil management and pathogen suppressive soils in southern Sweden : an interdisciplinary analysis - Löbmann, Michael (SLU/Dept. of People and Society, 2015)
A holistic study on soil-borne pathogen management with suppressive soils was performed in Scania, Sweden. The study was designed to comprise both social and biological research to gain a systemic perspective on the real-life situation of Swedish farmers regarding plant pathogens and soil management. The social research comprised semi-structured interviews with a small number of farmers and an online survey, which could not be sent to farmers and therefore was without results. Possible reasons for the failure are discussed. For the biological research, soils from ten Swedish farms with different cropping and management regimes were assessed for effects on Pythium ultimum disease symptoms in wheat, physical and chemical soil parameters, and the soil nematode trophic community as identified at the family level.